REFLECTING ON FORCED CHARACTER IN HUMAN DISPLACEMENT - Coraza de los Santos, Enrique; Gatica, Mónica Graciela (Revista de Historia Social y de las Mentalidades, 2019)
Forced displacement has many aspects to be considered: a phenomenon which has run through the history of Latin America and it is still a current issue today.  It takes on different forms in different countries and regions but remains a constant presence.Our main concern is to promote a debate about what this force displacement represents from a conceptual point of view as well as to differentiate between this and other types of migrationsWe hope to contribute to the continuing research that already exists in Southern America and the Central America-Mexico corridor on the specific characteristics of these displacements, whilst paying special attention to their diversity.
Keywords: Forced Displacement; Exile; Forced Migration; Internal Forced Displacement